Altered Mobility and Accumulation of Inefficient Workers in Juvenile Hybrid Termite Colonies - Lee, Sang-Bin; Chouvenc, Thomas; Patel, Jayshree; Su, Nan-Yao (Frontiers in Ecology and Evolution, 2020)
Hybridization of two different species is an important mechanism to have gene flows between species. Recently, mating of two economically important invasive species of subterranean termites (Coptotermes formosanus and Coptotermes gestroi) have been observed in the field and hybrids colonies have been established in the laboratory. It was previously reported that incipient colonies ( 1yr old) of hybrid Coptotermes species contained more termites than colonies of parental species, showing hybrid vigor. In this study, colony vigor and individual termite vigor were investigated in juvenile colonies ( 2yr old), using colony growth parameters and the movement activity of individual termites as proxies for the evaluation of hybrid vigor beyond the initial colony foundation. After two years from colony foundations, hybrid colonies showed no more hybrid vigor. In addition, movement activity of termites in hybrid colonies was significantly slower than in termites from conspecific colonies. It is suggested that a reduction in the molting rates of individuals in hybrid colonies may have a negative impact on their physiology and their movement activity. These possible changes in physiology may affect the movement of individuals, and accumulation of these inefficient termites in hybrid colonies may contribute to the loss of hybrid vigor at two years of age in hybrid colonies.